A paisagem nas aulas de geografia: práticas de ensino e o olhar de jovens escolares do ensino médio de Goiânia - Felício, Willian Franco (2021)
The present work aims to present a theoretical discussion regarding the landscape in geographic science, in order to understand it as an important analytical category in the field of research on the teaching of geography, in addition to being a relevant tool in the promotion of a teaching practice that promotes more relevant teaching to young students. Based on theoretical references such as Santos (1997), Maximiliano (2004), Bertrand (2004), Brito and Ferreira (2011), Moreira (2015) and Gomes (2017) about landscape, we seek to present a contextualization of the definitions of this category in the didactic construct of school geography based on the works of Callai (2005), Castellar 2013, 2017), Cavalcanti (2004,2008,2017,2019), Freire (2018), Pinheiro (2015), Pires (2020) and Puntel (2020). In addition to the bibliographical research, classroom observations and three intervention proposals were carried out, through synchronous classes in the remote model due to the pandemic context, with 1st grade high school students seeking to work the teaching of Geography from the landscape with a focus the urban landscape of the city of Goiânia. We understand the importance of landscape in the process of teaching practice for the teaching of geography, as we understand that it enables the expansion of students' perspective and allows students to approach the studied object, seeking to develop in these students the ability to understand different landscapes, their elements , its history, its social and cultural practices and its natural dynamics in order to favor the formation of citizens of these young students.